Catalytic Synthesis of Oligosiloxanes Mediated by an Air Stable Catalyst, (C6F5)3B(OH2) - Rabanzo-Castillo, Kristel M.; Kumar, Vipin B.; Söhnel, Tilo; Leitao, Erin M. (Frontiers in Chemistry, 2020)
The utility of (C6F5)3B(OH2) as catalyst for the simple and environmentally benign synthesis of oligosiloxanes directly from hydrosilanes, is reported. This protocol offers several advantages compared to other methods of synthesizing siloxanes, such as mild reaction conditions, low catalyst loading, and a short reaction time with high yields and purity. The considerable H2O-tolerance of (C6F5)3B(OH2) promoted a catalytic route to disiloxanes which showed >99% conversion of three tertiary silanes, Et3SiH, PhMe2SiH and Ph3SiH. Preliminary data on the synthesis of unsymmetrical disiloxanes (Si-O-Si’) suggests that by modifying the reaction conditions and/or using a 1:1 combination of silane to silanol the cross-product can be favoured. Intramolecular reactions of disilyl compounds with catalytic (C6F5)3B(OH2) led to the formation of novel bridged siloxanes, containing a Si-O-Si linkage within a cyclic structure as the major product. Moreover, the reaction conditions enabled recovery and recycling of the catalyst. The catalyst was re-used 5 times and demonstrated excellent conversion for each substrate at 1.0 mol% catalyst loading. This seemingly simple reaction has a rather complicated mechanism. With the hydrosilane (R3SiH) as the sole starting material, the fate of the reaction largely depends on the creation of silanol (R3SiOH) from R3SiH as these two undergo dehydrocoupling to yield a disiloxane product. Generation of the silanol is based on a modified Piers-Rubinsztajn reaction. Once the silanol has been produced, the mechanism involves a series of competitive reactions with multiple catalytically relevant species involving water, silane and silanol interacting with the Lewis acid and the favoured reaction cycle depends on the concentration of various species in solution.